Diabetic kidney disease: new treatment options. (March 2013) - Thomas, Merlin C
SUMMARY There is an urgent need for new approaches to protect the kidney and its functions in the increasing number of patients with diabetes. Although current strategies are effective, their effect is only partial and the majority of cases are not prevented, even by best practice. A number of new targets have been proposed, including direct renin inhibition, inhibition of fibrosis, activation of Nrf-2, sulodexide, endothelin I and urotensin II. However, the most advanced of these have all recently failed, while the remainder have demonstrated plausible efficacy only in small underpowered studies, and much research remains to both establish their efficacy and get them to the clinic. The development of better-targeted ('smarter') drugs appears to be the best hope for renoprotective therapy in the future.